北極域観測用新型ナトリウムライダーの現状 - 川原, 琢也; 野澤, 悟徳; 津田, 卓雄; 川端, 哲也; 藤井, 良一; 斎藤, 徳人; 和田, 智之; Takuya, D. Kawahara; Satonori, Nozawa; Takuo, Tsuda; Tetsuya, Kawabata; Ryoichi, Fujii; et al. (2010)
第34回極域宙空圏シンポジウム 12月2日（木） 国立極地研究所 2階大会議室 conference object